Entrepreneurial Leadership and Organizational Resilience in Islamic Philanthropy: A Case Study of LAZISNU Doro, Indonesia - Mufid, Muhammad; Elizabeth , Misbah Zulfa (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2025)
The effectiveness of an organization’s work program often hinges on the leader’s capacity to manage and direct the organization. This study examines the entrepreneurial leadership demonstrated by LAZISNU in the Doro District in its efforts to enhance organizational independence. A qualitative descriptive case study approach was employed, with data collected using triangulation of data sources, methods, and theories to ensure the validity and reliability of the findings. The analysis reveals that LAZISNU Doro, Pekalongan, Indonesia exhibits an entrepreneurially oriented leadership model, characterized by proactively fostering organizational commitment through the alignment of vision and mission to cultivate a positive work culture; implementing innovative and collaborative programs by leveraging social influence from community leaders and women's religious organizations (Muslimat and Fatayat Nahdlatul Ulama) to enhance productivity; taking strategic risks through partnerships that support community services and member skill development; and upholding organizational integrity and religious values to build public trust. These findings contribute to the empirical literature on religious organizational development, confirming that modern entrepreneurial principles are not only applicable to for-profit ventures but are also instrumental in the success of non-profit organizations. The case of LAZISNU Doro illustrates how effective leadership in non-profit settings can serve as a catalyst for community empowerment and socio-economic transformation